Kandungan Logam Berat Pb dan Zn Dalam Organ Ikan Baung (Hemibagrus nemurus) dari Dua Danau Oxbow di Kecamatan Siak Hulu, Kampar - Hendra Rezki; Budijono Budijono; M. Hasbi M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractLubuk Siam Lake and Pinang Dalam Lake are oxbow lakes formed due to the interruption of the Kampar River flow. Fish is one of the aquatic biota which can be used as an indicator of the level of pollution that occurs in the waters. Asian Redtail Catfish (Hemibagrus nemurus) inland fisheries that has economic value and is often caught by fishermen around the lake. The purpose of this study was to determine the content of heavy metals Pb and Zn which accumulate in the skin, liver, and kidney organs of the fish in the two lakes. Organ samples were collected and digested according to standard procedures to determine the concentrations of heavy metals Pb and Zn tested using Atomic Absorption Spectrophotometry (AAS). The results showed that the highest and lowest heavy metals were in the organ of Asian Redtail Catfish in Lubuk Siam Lake, namely Pb (kidney> liver> skin) and Zn (kidney> liver> skin), while for Pinang Dalam Lake, namely: Pb (liver> skin). > kidney) and Zn (kidney> skin> liver).Keywords: Heavy metal,  baung fish, organs, Pinang Dalam Lake.